(untitled) - Cunningham, Hart (Fairfield, CT, 2007)
Maximizing Me, 30 Lessons on the Journey to Self-Empowerment invites you to embrace your dreams, discover the path you with to take, resolve inner conflicts, and reinvent your life. Throughout the pages, Cunningham challenges you to reject past mistakes and move forward with a clear mind.
Keywords: Sự thành đạt,Thành công trong kinh doanh,Success,Success in business,Self-help techniques